INFORMATION AND COMMUNICATION TECHNOLOGIES INFLUENCE ON LIBRARIAN’S SKILLS IN NEPAL (LIS TODAY, 2023)
This study explores the impact of Information and Communication Technology (ICT) on  librarians employed at five specifically chosen university libraries in Nepal. The research  used a structured questionnaire as a data collection tool. The research engaged all five  university librarians, and all distributed questionnaires were completed and returned. The  study's findings indicate that while university librarians demonstrated competence in  fundamental ICT applications, there is a recognized need for additional knowledge  acquisition to achieve proficiency in specific ICT tools. Moreover, all surveyed librarians  strongly agreed that integrating ICT applications contributes positively to the stature of  libraries.
Keywords: ICT skills; ICT competencies; University Libraries; Library professionals; Nepal